Conceptualizing the NET: The Neuroeducation Translational (NET) research model – a framework for neuroscience research to special education practice - Kosaraju , Sagarika; Gorman , Mary; Berry , Katherine (Journal of Interdisciplinary Studies in Education, 2014)
Advances in neuroscience related to developmental disorders could substantially impact individuals with disabilities and the field of special education.  However, several challenges impede the current translation of neuroscience research for special education practice, such as misinterpretations of neuroscience findings.  An investigation of translational research in medicine and social sciences revealed a common conceptual framework founded by the National Institutes of Health (NIH).  Using this model as a guide, the authors introduce a new framework, the Neuroeducation Translational (NET) Research Model, to scaffold neuroscience research from the laboratory to special education practice in four phases.  Potential benefits to developing a framework for neuroeducation include improved outcomes for individuals with disabilities and knowledge sharing across disciplines.